2007
DOI: 10.1210/jc.2007-1211
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Medullary Thyroid Carcinoma with Persistent Elevated Calcitonin Levels

Abstract: The most efficient imaging work-up for depicting MTC tumor sites would consist of a neck US, chest CT, liver MRI, bone scintigraphy, and axial skeleton MRI. FDG PET scan appeared to be less sensitive and of low prognostic value.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
148
1
23

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 233 publications
(180 citation statements)
references
References 34 publications
5
148
1
23
Order By: Relevance
“…For local or regional recurrence in the neck and mediastinum, reoperation is the main treatment. However, cure is achieved only in 5-35% of the reoperated patients, and the remainder of patients are at high risk of developing distant metastasis (Wells et al 1982, Giraudet et al 2007. Distant metastases that are observed at presentation in 7-23% of unselected patients with MTC are the main cause of MTC-related death with survival rates of 25% at 5 years after their detection (Bergholm et al 1997, Modigliani et al 1998.…”
Section: Introductionmentioning
confidence: 99%
“…For local or regional recurrence in the neck and mediastinum, reoperation is the main treatment. However, cure is achieved only in 5-35% of the reoperated patients, and the remainder of patients are at high risk of developing distant metastasis (Wells et al 1982, Giraudet et al 2007. Distant metastases that are observed at presentation in 7-23% of unselected patients with MTC are the main cause of MTC-related death with survival rates of 25% at 5 years after their detection (Bergholm et al 1997, Modigliani et al 1998.…”
Section: Introductionmentioning
confidence: 99%
“…Diagnosis of the sporadic form is usually established late in life (approximately the fifth or sixth decade). Neck lymph node metastases are detected in approximately 50% of cases at the time of diagnosis, while distant metastases occur in 20% of cases (8)(9)(10)(11) (B). Early surgical intervention is the only curative therapeutic approach (11) (B).…”
Section: (A/b)mentioning
confidence: 99%
“…Neck metastases appear early during the course of MTC (9,65) (B). Distant metastases are detected in 7-17% of all cases at the time of diagnosis and frequently appear in multiple sites (lungs, liver, bones, and less often in the brain and skin) (10,11,66,67) Individuals with hereditary MTC should be screened for pheochromocytoma, given their high risk of that disease (72) (B). As up to 10% of apparently sporadic MTC have a RET germline mutation, the presence of pheochromocytoma should be excluded in any patient with suspected MTC before the thyroidectomy, due to the high risk of anesthesia and the surgical procedure (73,74)(D/B).…”
Section: Recommendationmentioning
confidence: 99%
“…Two studies showed that FDG PET/CT outperforms CT and MRI for the detection of neck and mediastinal disease, but is inferior to CT for the detection of lung and liver metastases, and to MRI for the identification of metastases to bone [17,18]. Three studies have examined serum Ct levels and the likelihood of a positive FDG PET scan.…”
mentioning
confidence: 99%